Supplement I. To a Catalogue of Official Reports Upon Geological Surveys of the United States and Territories, and of British North America - Frederick Prime (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1880)
IN this supplementary list no titles to which an * is prefixed have been seen by the compiler; and he will be most thankful to have any omissions or inaccuracies in the list sent to him to be published as a second supplement in the next volume of the Transactions. The author is indebted to Messrs. Robert Clarke, of Cincinnati ; Thomas Macfarland, of Towanda; Professor F. W. Simouds, of Chapel Hill; and Professor J. J. Stevenson, of New York, for valuable assistance. CEDAR POINT IRON COMPANY, BALTIMORE, July 31st, 1880. ALABAMA. Geological Survey of Alabama. Report of Progress for 1877 and 1878 ; by Eugene A. Smith, State Geologist. Montgomery, 1879. 8vo., 139 pp., and 4 maps.